Controllable Si−C Bond Activation Enables Stereocontrol in the Palladium‐Catalyzed [4+2] Annulation of Cyclopropenes with Benzosilacyclobutanes - Wang, Xing‐Ben; Zheng, Zhan‐Jiang; Xie, Jia‐Le; Gu, Xing‐Wei; Mu, Qiu‐Chao; Yin, Guan‐Wu; Ye, Fei; Xu, Zheng; Xu, Li‐Wen (Angewandte Chemie International Edition, 2020)
A novel and unusual palladium‐catalyzed [4+2] annulation of cyclopropenes with benzosilacyclobutanes is reported. This reaction occurred through chemoselective Si−C(sp2) bond activation in synergy with ring expansion/insertion of cyclopropenes to form new C(sp2)−C(sp3) and Si−C(sp3) bonds. An array of previously elusive bicyclic skeleton with high strain, silabicyclo[4.1.0]heptanes, were formed in good yields with excellent diastereoselectivity under mild conditions. An asymmetric version of the reaction with a chiral phosphoramidite ligand furnished a variety of chiral bicyclic silaheterocycle derivatives with good enantioselectivity (up to 95.5:4.5 er). Owing to the mild reaction conditions, the good stereoselectivity profile, and the ready availability of the functionalized precursors, this process constitutes a useful and straightforward strategy for the synthesis of densely functionalized silacycles. When Si−C meets C=C bond activation: Cyclopropenes were functionalized stereoselectively with benzosilacyclobutanes by palladium‐catalyzed Si−C(sp2) bond activation and a ring‐expansion/[4+2] annulation sequence to form new C(sp2)−C(sp3) and Si−C(sp3) bonds of silabicyclo[4.1.0]heptanes. The transformation provided an array of these previously elusive highly strained bicyclic skeletons in good yields with high selectivity (see scheme).